Leadership Strategy of Muhammadiyah Boarding School (MBS) Poncowati in Improving the Qur’anic Memorization Quality of Tahfidz Students - Hardiansyah, Irvan; Sujino, Sujino; Cahyono, Heri (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
This study investigates the method used by the leadership of the Muhammadiyah Boarding School (MBS) Poncowati Islamic Boarding School (MBS) to improve the students' memorization of the Qur'an through the tahfidz coaching program. The research started from the fact that the number of tahfidz institutions has increased, but it has not been fully accompanied by an improvement in the quality of memorization (mutqin) of students. This study uses a descriptive qualitative methodology with a case study design. The informants in this study included pesantren leaders, tahfidz ustadz, and students, who were selected purposively. Analysis, observation, and documentation are methods of data collection, and triangulation ensures the validity of the data. The research found five key components of a leadership strategy: a planned tahfidz curriculum; the implementation of routine coaching through Subuh, Muraja'ah Sore, and Tasmi' Pekanan deposits; the use of technology to monitor memorization; tiered evaluation; and moral and spiritual strengthening through gifts and examples. Improving the quality of students' memorization and forming a sustainable Qur'anic habitus are two goals that this approach has successfully achieved. This study supports the theory of Islamic education management and pesantren leadership and provides a strategic model that can be applied by other tahfidz institutions.